What the Bible really tells us : the essential guide to biblical literacy - Wray, T. J. (Rowman & Littlefield : Distributed by National Book Network, 2011)
The Bible is the foundational text for Jews and Christians, but most people, having little knowledge of what it actually says, feel less than comfortable navigating its pages. What the Bible Really Tells Us solves this problem, providing a thorough, yet accessible, guide to the Good Book and the ways in which it can enrich one's life. Opening with a 60-Second Super-Easy Bible Quiz to test a reader's knowledge, author T.J. Wray provides essential background information to arm readers with the tools necessary to read and interpret passages on their own. And, with these tools in hand, Wray helps readers explore what the Bible really says about key issues today, including suffering, heaven and hell, gender and sexuality, [and] the environment.--Amazon.com.